THE CASE OF THE DEBUT OF SYSTEMIC SCLERODERMA IN A PATIENT AGED 10 - А. V. BURLUTSKAYA; N. V. SAVELYEVA; A. V. STATOVA (Кубанский научный медицинский вестник, 2018)
Aim. To show the diversity and severity of clinical symptoms, a large range of diagnostic search, as well as difficulties in therapy in a 10-year-old patient with systemic manifestations of juvenile scleroderma.Materials and methods. A retrospective analysis of the anamnetic data, the course of the disease, laboratory and instrumental data, as well as the ongoing therapy of a 10-year-old patient with juvenile systemic scleroderma was carried out.Results. The patient was diagnosed with multiple typical sclerodermic foci of irregular shape, with different stages of lesion (edema, induration and atrophy). Joint damage was noted in the form of pseudoarthritis interphalangeal joints of hands with the formation of sclerodactily and right ankle joint. As a result of computed tomography of chest, signs of interstitial lung disease by the type of fibrous alveolitis have been revealed. After verification of the diagnosis, the patient was prescribed basic therapy: methylprednisolone and cyclophosphane.Conclusion. A clinical case of the debut of juvenile systemic scleroderma with rapidly progressive, widespread skin lesions, involvement of the musculoskeletal system and the development of fibrous alveolitis is presented. Due to intensive and long-term pathogenetic therapy (glucocorticoids, cyclophosphamide), the patient's condition was stabilized and the progression of interstitial lung disease was stopped.